Tingkat Penerapan Teknologi Budidaya pada Usahatani Vanili (Vanilla Planifolia) di Kecamatan Sapuran Kabupaten Wonosobo - Rahardina, Anggita Putri (Agritechpedia, 2023)
The purpose of this study was to identify the characteristics of vanilla farmers related to the level of application of cultivation technology in vanilla farming, examine the level of application of cultivation technology in vanilla farming, and examine the relationship between characteristics and the level of application of cultivation technology in vanilla farming by farmers. This study uses a quantitative descriptive method. The population in this study were all vanilla farmers in Sapuran District. The analytical method used is class interval width formula, Rank Spearman Correlation Coefficient Test (rs) at 95% confidence level. Based on the research results, the level of application of cultivation technology in vanilla farming by farmers in the aspects of seeding, maintenance, harvesting, and post-harvest is in the medium category, while the planting aspect is in the low category. The characteristics of farmers for the age variable are included in the moderate category. The land area is in the medium category with an area of between 100m2-600m2. The level of formal education is included in the moderate category, namely junior high school and high school graduation. Farmers' experience in cultivating vanilla is in the medium category, namely for 3-8 years. The intensity of counseling is in the low category, namely <1-3 times a year. The variable characteristics of vanilla farmers in Sapuran District, Wonosobo Regency, which are significantly related to the level of application of cultivation technology in vanilla farming, namely land area and experience, are not significantly related, namely age, level of education, and intensity of counseling.Keywords: Application Level, Cultivation Technology, Vanilla